INCLUSION IN ELEMENTARY SCHOOL CHILDREN IN RELATION TO THE IMPORTANCE OF PHYSICAL EDUCATION IN THE SOCIALIZATION OF STUDENTS IN COLOMBIA - Carmen Victoria Silva (LÍNEA IMAGINARIA, 2025)
Education in recent times is facing situations that are not very common due to the appearance and incorporation of artificial intelligences in the different ways of teaching and learning; to this effect, a set of contextualized factors are related to the development of pedagogical activities and, together with this, other situations have been added when, by provision of the legal norm, the obligation to receive students with exceptional characteristics in the classroom is indicated. From this perspective, it is convenient to rethink about the inclusion of children with special conditions to the regular teaching processes and then the following general objective arises: to analyze the theoretical postulates that originate from the inclusion of children in front of the relevance that physical education (EF) has from the socialization of students in Colombia. The methodology focuses on a documentary analysis related to a sample of educational inclusion and its relationship with EF; reason that brought as a result that physical education can improve as it is possible to reveal in the school progress of the students and their development in society. Therefore, it is pertinent to point out that it is based on a review focused on a historical review of educational inclusion and its relationship with the strengthening processes in the different ways of teaching PE; it is important to point out the remarkable conclusion reached, which is focused on the fact that by assuming educational inclusion from the different ways of teaching EF, a space for equality is opened, highlighting the effects that it brings to society in general.